Depositor discipline during crisis: Flight to familiarity or trust in local authorities? - Schoors, Koen; Semenova, Maria; Zubanov, Andrey (Journal of Financial Stability, 2019)
We analyze whether bank familiarity affects depositor behavior during financial crisis. Familiarity is measured by regional or local cues in the bank’s name. Depositor behavior is measured by the depositor’s sensitivity to observable bank risk (depositor discipline). Using 2001–2010 bank-level and region-level data for Russia, we find that depositors of familiar banks become less sensitive to bank risk during a financial crisis relative to depositors of unfamiliar banks. To validate that our results stem from a flight to familiarity during crisis and not from implicit guarantees from regional governments, we split our sample along the lines of regional affinity and trust in local governments. The flight to familiarity effect is strongly confirmed in the subsample of regions with strong regional affinity, while the effect is absent in the subsample of regions with more trust in regional and local governments, lending support to the thesis that our results are driven by a flight to familiarity rather than by implicit guarantees.